2012
DOI: 10.13057/biodiv/d130201
|View full text |Cite
|
Sign up to set email alerts
|

The conservation of mitochondrial genome sequence in Leucadendron (Proteaceae)

Abstract: Pharmawati M, Yan G, Finnegan PM. 2012. The conservation of mitochondrial genome sequence in Leucadendron (Proteaceae). Biodiversitas 13: 53-58. Mitochondrial DNA (mtDNA) is useful for developing molecular markers and for studying plant phylogeny. However, its usefulness depends on the degree of detectable sequence variation. In seven species of the genus Leucadendron, PCR-RFLP failed to reveal any polymorphisms in seven separate regions of the mtDNA. Sixty-two primer pair -enzyme combinations were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The mtDNA nad 1 b/c intron was approximately 1500 bp in length in this study, but has been found to vary in length among species, reaching up to 2100 bp (Demesure et al, 1995;Freudenstein and Chase, 2001;Sun, 2002;Mohanty et al, 2003). The nad 4 1/2 intron was approximately 2000 bp in length, in agreement with the length reported for the nad 4 intron in other plant species (Dumolin-Lapègue et al, 1998;Pharmawati et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The mtDNA nad 1 b/c intron was approximately 1500 bp in length in this study, but has been found to vary in length among species, reaching up to 2100 bp (Demesure et al, 1995;Freudenstein and Chase, 2001;Sun, 2002;Mohanty et al, 2003). The nad 4 1/2 intron was approximately 2000 bp in length, in agreement with the length reported for the nad 4 intron in other plant species (Dumolin-Lapègue et al, 1998;Pharmawati et al, 2012).…”
Section: Discussionsupporting
confidence: 89%